Biopolymer formulations

By developing biological polymer preparations containing radonic gelatin and methyl acrylic hyaluronic acid, and inducing cross -linking of hydrogels through light -induced agents, solving the problem of insufficient performance of the existing eye adhesive, and achieved efficient efficiency , Biocompatible corneal therapy effect.

CN119365222APending Publication Date: 2025-01-24PANDORUM TECH PTE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046723.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-28
Filing Date
2023-04-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing eye adhesives have suboptimal performance problems, such as rapid polymerization and heat generation, low biocompatibility, low transparency and rough surface, making it difficult to integrate with the receptor eye tissue, resulting in poor treatment results.

Method used

The development of a biological polymer preparation containing the radical gelatin and methyl acrylic hyaluronic acid, which induces the cross -linked hydrogel through light -induced agent, and matches the physical characteristics of natural cornea.

Benefits of technology

A highly efficient, biocompatible, and biodegradable hydrogel formulation with improved transparency, adhesive strength, degradation stability, and cell biocompatibility for the treatment of corneal diseases was achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005184668370000011
    Figure HDA0005184668370000011
  • Figure HDA0005184668370000012
    Figure HDA0005184668370000012
  • Figure HDA0005184668370000014
    Figure HDA0005184668370000014
Patent Text Reader

Abstract

The present disclosure provides a biopolymer formulation comprising a thiolated gelatin and a methacrylated hyaluronic acid. The formulations are useful in corneal applications, such as the treatment of a disease or injury of the cornea in a subject. Methods of preparing the biopolymer formulations and uses thereof are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Corneal blindness is the fourth leading cause of blindness in the world, with an estimated 1.5 million new cases reported globally each year. Approximately 10 million people worldwide suffer from bilateral corneal blindness, and an additional 23 million suffer from unilateral corneal blindness. The main causes of corneal dysfunction include trachoma (involving corneal scarring and vascularization), eye trauma, corneal ulcers, and infections (such as those caused by the herpes simplex virus). One of the key medical treatments for corneal diseases includes keratoplasty (corneal transplantation). However, corneal transplantation has various complications, including: (i) tissue (cornea) rejection in keratoplasty patients; (ii) scarring from infections, such as herpes or fungal keratitis in the eye; (iii) glaucoma (increased intraocular pressure); (iv) vision problems (sharpness of vision) caused by the irregular curve of the corneal shape; (v) corneal transplant detachment; and (vi) high costs and inconveniences surrounding the safe extraction, storage, and transportation of living tissue.

[0002] Given the limitations of corneal transplantation, various efforts have been made to reduce or eliminate the reliance on keratoplasty, such as biopolymer-based ocular adhesives that mimic the properties of the natural cornea once applied to a diseased, degenerated, damaged, or partially excised cornea. For example, such ocular adhesives can be used to close ocular wounds after injury or during corneal surgery. In corneal surgery, biopolymers can be used as a sutureless substitute for postoperative closure of perforations. Various biomaterials have been reported in the literature for the treatment of corneal damage caused by ocular diseases.

[0003] However, conventional ocular adhesives still suffer from suboptimal performance issues, including rapid polymerization and heat generation, low biocompatibility, low clarity and rough surface, difficult processing, short residence time, and poor integration with recipient ocular tissue.

[0004] Therefore, there has long been a need in the art to develop an efficient, biocompatible, and biodegradable cross-linked hydrogel formulation that matches the properties of the natural cornea, which would aid in the treatment of corneal diseases while avoiding side effects. Given (1) the remarkable physical properties of the cornea that combine high transparency and durability, and (2) the unpredictable effects of polymer chemistry and composition on the physical properties of the resulting hydrogels, generating hydrogels that are compatible with the natural cornea and have physical properties that match those of the natural cornea remains a daunting challenge. SUMMARY OF THE INVENTION

[0006] Provided herein are embodiments of biopolymer formulations comprising thiolated gelatin and methacrylated hyaluronic acid.

[0007] In some variations, the average molecular weight of thiolated gelatin may be about 50 kDa to about 200 kDa, and the average degree of substitution may be about 0.2 mmol / g to about 1.2 mmol / g; and the average molecular weight of methacrylated hyaluronic acid may be 20-80 kDa, and the average degree of substitution may be 0.5-1 mmol / g.

[0008] In some variations, the biopolymer formulation may include: thiolated gelatin having a bloom value of about 200 bloom to about 275 bloom and an average degree of substitution of about 0.5 mmol / g to about 0.9 mmol / g; and methacrylated hyaluronic acid having an average molecular weight of 25-40 kDa and an average degree of substitution of about 0.7 mmol / g to about 0.9 mmol / g, wherein the weight ratio of thiolated gelatin to methacrylated hyaluronic acid is about 100:30 to about 100:70. Optionally, the bloom value of thiolated gelatin may be about 220 bloom to about 230 bloom, and the average degree of substitution may be about 0.5 mmol / g and about 0.7 mmol / g, and the weight ratio of thiolated gelatin to methacrylated hyaluronic acid may be about 100:55 to about 100:65. Optionally, the bloom value of the thiolated gelatin may be about 240 bloom to about 260 bloom, and the average degree of substitution may be about 0.7 mmol / g to about 0.9 mmol / g, and the weight ratio of the thiolated gelatin to the methacrylated hyaluronic acid may be about 100:35 to about 100:45.

[0009] In some variations, the biopolymer formulation may be in the form of a dry premix wherein the methacrylated hyaluronic acid and the thiolated gelatin are in the form of dry powders.

[0010] In some variations, the biopolymer formulation may be in the form of a liquid or hydrogel and may include a saline solution and at least one photoinitiator compound.

[0011] Also provided herein are embodiments of methods for treating corneal disease or injury in a subject. In some variations, the method may include: mixing a dry biopolymer premix comprising thiolated gelatin and methacrylated hyaluronic acid with a photoinitiator solution to produce a liquid biopolymer mixture; applying the liquid biopolymer mixture to the cornea of ​​the subject; and exposing the liquid biopolymer mixture applied to the cornea to light having a wavelength within the excitation range of at least one photoinitiator. In some variations, the dry biopolymer premix may include: thiolated gelatin, optionally having an average molecular weight of 50-200 kDa and an average degree of substitution of 0.2-1.2 mmol / g; and methacrylated hyaluronic acid, optionally having an average molecular weight of 20-80 kDa and an average degree of substitution of 0.5-1 mmol / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate certain aspects of the subject matter disclosed herein and, together with the description, help explain some principles associated with the disclosed embodiments.

[0013] Figures 1A-1C It is shown that after 1 day of culture ( Figure 1A )、2 weeks( Figure 1B ) and 4 weeks ( Figure 1C ) and stained with Calcein AM, ethidium homodimer, and DAPI to assess cell viability.

[0014] Figures 1D-1F It is shown that after 1 day of culture ( Figure 1D )、2 weeks( Figure 1E ) and 4 weeks ( Figure 1F hCSSCs grown in Gel-SH hydrogels after ELISA and stained with Calcein AM, ethidium homodimer, and DAPI to assess cell viability.

[0015] Figures 2A-2C It is shown that after 1 day of culture ( Figure 2A )、2 weeks( Figure 2B ) and 4 weeks ( Figure 2C ) and then grown in coverslip culture and stained with CD90, αSMA, and DAPI to assess cell differentiation.

[0016] Figure 2D-2F hCSSCs grown within Gel-SH hydrogels and stained with CD90, αSMA, DAPI to assess cell differentiation are shown after 1 day ( FIG. 2D ), 2 weeks ( FIG. 2E ), and 4 weeks ( FIG. 2F ) in culture.

[0017] Figure 3A-3B Phase contrast images of hCEC cells grown on coverslips for 4 days are shown, compared with those grown on the coverslip surface ( Figure 3A ) and hydrogel surface ( Figure 3B ) on hCECs.

[0018] Figures 4A-4C Shown are the cells grown on the coverslip surface and labeled with DAPI ( Figure 4A )、ZO1( Figure 4B ) and rhodamine phalloidin ( Figure 4C ) stained hCEC cells.

[0019] Figures 4D-4F shows the growth on the hydrogel surface and stained with DAPI ( Figure 4D )、ZO1( Figure 4E ) and rhodamine phalloidin ( Figure 4F) stained hCEC cells. DETAILED DESCRIPTION OF THE INVENTION

[0021] Non-limiting embodiments of various aspects and variations of the invention are described herein.

[0022] Embodiments of biopolymer formulations are provided herein.In some variations, the biopolymer formulations can be used to produce hydrogels that are compatible with the natural cornea and match its physical properties.

[0023] In some variations, the biopolymer formulation comprises: thiolated gelatin (Gel-SH) and methacrylated hyaluronic acid (HA-MA). Gel-SH is a gelatin modified with a thiol group. HA-MA is a hyaluronic acid modified with a methacrylate. Without being bound by theory or mechanism, modification of a polymer such as hyaluronic acid with a methacrylate crosslinks the polymer. The crosslinking may be a dimethacrylate crosslink between two methacrylate groups (e.g., between two HA-MA molecules), a thiol-ene crosslink between a methacrylate group and a thiol group (e.g., between a Gel-SH molecule and a HA-MA molecule), or a combination thereof. The crosslinking may be induced by a photoinitiator compound in the presence of light. Examples of photoinitiator compounds for methacrylate crosslinking include eosin (e.g., eosin Y), and / or triethanolamine.

[0024] Characteristics of Gel-SH

[0025] In some variations, the average molecular weight of the gel-SH of the biopolymer formulations of the present disclosure may be from about 50 kDa to about 200 kDa, from about 50 kDa to about 100 kDa, from about 40 kDa to about 120 kDa, from about 60 kDa to about 90 kDa, from about 60 kDa to about 150 kDa, about 50 kDa, about 60 kDa, about 70 kDa, about 80 kDa, about 90 kDa, about 100 kDa, about 120 kDa, about 140 kDa, about 160 kDa, about 180 kDa, and about 200 kDa. The average molecular weight of the gel-SH can be determined by size exclusion chromatography (SEC), or based on the bloom value determined by a gel analyzer.

[0026] In some variations, the average degree of substitution of gel-SH included in the formulation may be from about 0.2 mmol / g to about 1.2 mmol / g, from about 0.2 mmol / g to about 0.9 mmol / g, from about 0.3 mmol / g to about 0.9 mmol / g, from about 0.5 mmol / g to about 0.9 mmol / g, from about 0.3 mmol / g to about 0.8 mmol / g, from about 0.3 mmol / g to about 0.7 mmol / g, from about 0.65 mmol / g to about 0.75 mmol / g, from about 0.2 mmol / g, about 0.3mmol / g, about 0.4mmol / g, about 0.5mmol / g, about 0.6mmol / g, about 0.62mmol / g, about 0.64mmol / g, about 0.66mmol / g, about 0.68mmol / g, about 0.7mmol / g, about 0.72mmol / g, about 0.75mmol / g, about 0.8mmol / g, about 0.9mmol / g, about 1mmol / g, about 1.1mmol / g or about 1.2mmol / g.

[0027] In some variations, the bloom value of Gel-SH is about 100 bloom to about 300 bloom, about 200 bloom to about 300 bloom, about 100 bloom to about 150 bloom, about 150 bloom to about 250 bloom, about 200 bloom to about 250 bloom, about 200 bloom to about 275 bloom, about 220 bloom to about 260 bloom, about 220 bloom to about 280 bloom, about 210 bloom to about 240 bloom, about 100 bloom, about 120 bloom, about 125 bloom, about 150 bloom, about 175 bloom, about 200 bloom, about 215 bloom, about 225 bloom, about 240 bloom, about 250 bloom, about 260 bloom, about 270 bloom, about 280 bloom, about 290 bloom or about 300 bloom.

[0028] Characteristics of HA-MA

[0029] In some variations, the average molecular weight of HA-MA in the biopolymer formulations of the present disclosure may be from about 20 kDa to about 80 kDa, from about 30 kDa to about 60 kDa, from about 20 kDa to about 50 kDa, from about 30 kDa to about 40 kDa, from about 30 kDa to about 35 kDa, about 25 kDa, about 28 kDa, about 30 kDa, about 33 kDa, about 35 kDa, about 40 kDa, about 45 kDa, about 50 kDa, about 60 kDa, about 70 kDa, and about 80 kDa. The average molecular weight of HA-MA can be determined by size exclusion chromatography (SEC).

[0030] In some variations, the average degree of substitution of HA-MA in the biopolymer formulations of the present disclosure may be from about 0.5 mmol / g to about 1 mmol / g, from about 0.6 mmol / g to about 1 mmol / g, from about 0.7 mmol / g to about 0.9 mmol / g, about 0.5 mmol / g, about 0.6 mmol / g, about 0.7 mmol / g, about 0.75 mmol / g to about 0.8 mmol / g, 0.81 mmol / g, 0.85 mmol / g, or about 0.9 mmol / g.

[0031] Dry premix

[0032] In some variations, the biopolymer formulations of the present disclosure may be in the form of dry premix formulations, wherein Gel-SH and HA-MA are in the form of dry powders, optionally lyophilized. In some variations, Gel-SH and HA-MA may be uniformly mixed and stored in a sterile container for reconstitution with water, physiologically compatible saline solution (optionally buffered saline); such reconstitution may be performed at the site of corneal surgery, for example, at the bedside. Optionally, Gel-SH and HA-MA are premixed in the form of a solution. Gel-SH and HA-MA may be preliminarily solubilized together in water or saline in the desired proportions, and then dried (lyophilized) after solubilization, so that the resulting powder becomes a completely mixed mixture of Gel-SH and HA-MA. The preliminary solubilization may be performed in a dark environment or in a container with light shielding and / or without a photoinitiator to prevent premature crosslinking, so that the Gel-SH and HA-MA in the premix remain uncrosslinked after the preliminary solubilization and drying.

[0033] In some variations, Gel-SH and HA-MA may be mixed in a dry premix at a weight ratio (Gel-SH:HA-MA) of about 100:30 to about 100:90, about 100:30 to about 100:70, about 100:30 to about 100:60, about 100:40 to about 100:70, about 100:50 to about 100:70, about 100:40, about 100:50, about 100:60, about 100:70, or about 100:80.

[0034] In some variations, the dry premix may further comprise: a therapeutic agent, also in dry or lyophilized form. Exemplary therapeutic agents include, but are not limited to, exosomes and liposomes.

[0035] Hydrogel

[0036] In some variations, the biopolymer formulations of the present disclosure may be in the form of a liquid biopolymer mixture in which Gel-SH and HA-MA are not (or minimally) cross-linked, or may be in the form of a hydrogel in which Gel-SH and HA-MA are generally cross-linked and Gel-SH and HA-MA are in aqueous solution. In the form of a liquid biopolymer mixture or a hydrogel, the biopolymer formulation may include: an aqueous solvent. In some variations, the aqueous solvent may be water or saline. The saline may be a physiological saline having an osmotic pressure or an osmotic pressure compatible with tissue (e.g., cornea). The saline may be a buffered saline, such as phosphate buffered saline (PBS).

[0037] In some variations, gel-SH and HA-MA can be cross-linked to form a hydrogel. Cross-linking can include dimethacrylate cross-linking between HA-MA molecules and / or thiol-ene cross-linking between gel-SH molecules and HA-MA molecules. The HA-MA in the liquid biopolymer liquid or hydrogel can be about 0% to about 100% cross-linked, about 10% to about 90% cross-linked, about 20% to about 80% cross-linked, uncross-linked, about 5% cross-linked, about 10% cross-linked, about 15% cross-linked, about 20% cross-linked, about 25% cross-linked, about 30% cross-linked, about 40% cross-linked, about 50% cross-linked, about 60% cross-linked, about 70% cross-linked, about 80% cross-linked, about 90% cross-linked, or about 100% cross-linked.

[0038] In some variations, the liquid biopolymer mixture or biopolymer formulation in the form of a hydrogel may include Gel-SH at a concentration of about 50 mg / ml to about 140 mg / ml, about 70 mg / ml to about 140 mg / ml, about 75 mg / ml to about 125 mg / ml, about 90 mg / ml to about 110 mg / ml, about 90 mg / ml to about 130 mg / ml, about 100 mg / ml to about 120 mg / ml, about 70 mg / ml, about 75 mg / ml, about 80 mg / ml, about 90 mg / ml, about 100 mg / ml, about 110 mg / ml, about 120 mg / ml, about 125 mg / ml, about 130 mg / ml, or about 140 mg / ml.

[0039] In some variations, the liquid biopolymer mixture or biopolymer formulation in the form of a hydrogel may contain HA-MA at a concentration of about 40 mg / ml to about 90 mg / ml, about 40 mg / ml to about 70 mg / ml, about 45 mg / ml to about 65 mg / ml, about 50 mg / ml to about 60 mg / ml, about 40 mg / ml, about 45 mg / ml, about 50 mg / ml, about 55 mg / ml, about 60 mg / ml, about 65 mg / ml, about 70 mg / ml, about 75 mg / ml, or about 80 mg / ml.

[0040] In some variations, the liquid biopolymer mixture or the biopolymer formulation in the form of a hydrogel may include at least one photoinitiator. The photoinitiator is typically a compound or combination of compounds that catalyzes the crosslinking of functionalized polymers such as HA-MA and / or gel-SH. In some variations, at least one photoinitiator includes eosin, triethanolamine, or a combination thereof. In some variations, eosin is eosin Y. In some variations, the biopolymer formulation may include eosin Y at a concentration of about 0.02 mM to about 0.2 mM, about 0.05 mM to about 0.2 mM, about 0.05 mM to about 0.1 mM, about 0.05 mM, about 0.08 mM, about 0.1 mM, or about 1.5 mM. In some variations, the biopolymer formulation may include Eosin Y at a concentration of about 0.02% v / v to about 0.2% v / v, about 0.05% v / v to about 0.2% v / v, about 0.02% v / v to about 0.1% v / v, about 0.05% v / v to about 0.1% v / v, about 0.07% v / v to about 0.09% v / v, about 0.6% v / v, about 0.7% v / v, about 0.76% v / v, about 0.8% v / v, about 0.9% v / v, or about 1% v / v.

[0041] In some variations, the liquid biopolymer mixture or the biopolymer formulation in the form of a hydrogel may include a therapeutic agent. The therapeutic agent may be a therapeutic exosome or liposome.

[0042] Method for preparing biopolymer hydrogel

[0043] In some variations, a biopolymer hydrogel according to embodiments of the present disclosure may be prepared by mixing a dry biopolymer premix and a photoinitiator solution to prepare a liquid biopolymer mixture, applying the liquid biopolymer mixture to a surface, and exposing the liquid biopolymer mixture applied to the surface to light having a wavelength within the excitation (absorption) range of the photoinitiator. For example, the exemplary photoinitiator Eosin Y has an excitation range of about 440 nm to about 575 nm, with a peak absorption of about 525 nm. The light may be white light containing mixed wavelengths including wavelengths within the excitation range of the photoinitiator.

[0044] In some variations, the liquid biopolymer mixture may include a therapeutic agent mixed with the dry biopolymer premix and the photoinitiator solution. The therapeutic agent may be mixed in dry or lyophilized form, optionally contained in the premix, contained in the second solution, or contained in the photoinitiator solution. In some variations, the therapeutic agent may be a therapeutic exosome or liposome.

[0045] The surface to which the liquid biopolymer mixture is applied and then crosslinked by exposure to form a crosslinked hydrogel can be a biological surface. The biological surface can be a tissue, such as a cornea. The cornea can be a diseased, degenerated, damaged or partially excised cornea.

[0046] Treatment

[0047] Compared to conventional hydrogels used as ocular adhesives, the biopolymer formulations of the present disclosure in hydrogel form exhibit one or more of the following improvements: improved clarity, improved bond strength, lower swelling (measured by weight and / or volume), reduced degradation over time, a compression modulus that is more compatible with tissues (such as the cornea), and improved biocompatibility with cells (such as corneal cells). Therefore, it may be advantageous to use the biopolymer formulations of the present disclosure as an ocular adhesive or temporary corneal substitute to treat corneal damage or corneal disease.

[0048] In some variations, a method of treating a corneal disease or injury in a subject may include: providing a liquid biopolymer mixture of the present disclosure comprising a photoinitiator; applying the liquid biopolymer mixture to a corneal wound site of the subject; and exposing the liquid biopolymer mixture applied to the cornea to light with a wavelength within the excitation range of the photoinitiator, such that the liquid biopolymer mixture crosslinks at the corneal wound site and forms a hydrogel replacement cornea (HRC). The corneal wound site may be a wound site excavated by, for example, corneal trephination to remove diseased, scarred, or damaged corneal tissue. The HRC may provide an environment that stimulates corneal regeneration, such that the HRC is replaced over time by regenerated corneal tissue formed at the corneal wound site.

[0049] In some variations, the liquid biopolymer mixture may be applied to the eye of a subject as follows: (1) surgically excavating and removing the diseased, damaged, or scarred cornea, such as by corneal trephination; (2) applying an appropriate volume of the liquid biopolymer mixture to fill gaps in the corneal tissue; (3) projecting white light of appropriate intensity onto the application site to crosslink the liquid biopolymer mixture and convert the mixture into HRCs. In some variations, after the HRCs are formed, the site may be washed with saline and treated with an antibiotic (e.g., moxifloxacin). In some variations, the cornea may be covered with a bandage contact lens for additional protection of the surgical site.

[0050] In some variations, the white light used to crosslink the liquid biopolymer mixture may be 1-100 mW / cm 2 10-100mW / cm 2 , 5-50mW / cm 2 , 5-20mW / cm 2 , 8-12mW / cm 2 、80-100mW / cm 2 , about 5mW / cm 2 , about 8mW / cm 2 , about 10mW / cm 2 , about 12mW / cm 2 , about 15mW / cm 2 , about 20mW / cm 2 , about 30mW / cm 2 , about 40mW / cm 2 , about 60mW / cm 2 , about 80mW / cm 2 or about 100mW / cm 2 The duration of light application may be 5-20 min, 5-10 min, 6-8 min, about 5 min, about 6 min, about 8 min, about 10 min, or about 12 min. Lower intensities may require longer durations, while shorter durations may be sufficient to achieve higher intensities.

[0051] In some variations, a liquid biopolymer mixture may be produced by mixing a dry biopolymer premix of the present disclosure and a photoinitiator solution of the present disclosure.

[0052] In some variations, the liquid biopolymer mixture may include one or more therapeutic agents useful for treating corneal disease or injury. Optionally, the one or more therapeutic agents may include therapeutic exosomes or liposomes.

[0053] Corneal diseases may be anterior corneal scarring involving epithelial and stromal damage / infection (active inflammation), stage 1 neurotrophic keratitis (NK) (persistent corneal epithelial defects), stage 2 NK (large persistent epithelial defects characterized by smooth, curled edges), stage 3 NK (deep corneal ulcers, stromal melting, and sterile hypopyon), corneal ulcers (such as Mooren's ulcers, keratoconus, corneal perforations, or corneal damage caused by dry eyes). Corneal diseases may include: limbal damage and corneal dystrophy (CD), such as type 1 lattice CD, type 1 granular CD, and congenital stromal CD, in which the corneal stroma of the subject is damaged. Corneal diseases may include: Schnyder's CD or type 2 lattice CD, in which both the epithelium and the stroma are damaged. Example

[0054] Example 1 - Production of Liquid Biopolymer Formulations and Hydrogels

[0055] The first exemplary liquid biopolymer formulation ("Formulation 1") was produced as follows: A dry premix was produced comprising Gel-SH (research grade bovine gelatin from Sigma-Aldrich; functionalized by Blafar, Inc.) and HA-MA (HA from Stanford Chemicals; functionalized by Blafar, Inc.) in a weight ratio of 100:60 (Gel-SH:HA-MA). The average molecular weight of Gel-SH was between 50-100 kDa (about 225 bloom) and the average degree of substitution was about 0.6 mmol / g. The average molecular weight of HA-MA was about 33 kDa and the average degree of substitution was about 0.81 mmol / g. The Gel-SH / HA-MA dry premix was mixed with a photoinitiator solution comprising Eosin Y and triethanolamine in a saline solution. The resulting liquid biopolymer mixture contained Eosin Y at a concentration of 0.05-0.1 mM, triethanolamine at a concentration of about 0.076% w / v, Gel-SH at a concentration of about 100 mg / ml, and HA-MA at a concentration of about 60 mg / ml.

[0056] A second exemplary liquid biopolymer formulation ("Formulation 2") was produced as follows: A dry premix was produced comprising Gel-SH (clinical grade gelatin from beMatrix, Nitta; functionalized by Blafar, Inc.) and HA-MA (HA from Stanford Chemicals; functionalized by Blafar, Inc.) in a weight ratio of 120:50 (Gel-SH:HA-MA) (compared to 100:60 in Gel-SH hydrogel 1). The average molecular weight of Gel-SH was about 100 kDa (250 Bloom) and the average degree of substitution was about 0.8 mmol / g. The average molecular weight of HA-MA (HA from Stanford Chemicals; functionalized by Blafar, Inc.) was about 33 kDa and the average degree of substitution was about 0.81 mmol / g. The Gel-SH / HA-MA dry premix was mixed with a photoinitiator solution comprising Eosin Y and triethanolamine in a saline solution. The resulting liquid biopolymer mixture contained Eosin Y at a concentration of 0.05 mM, triethanolamine at a concentration of about 0.076% w / v, Gel-SH at a concentration of about 120 mg / ml, and HA-MA at a concentration of about 50 mg / ml.

[0057] The procedure for preparing the liquid biopolymer mixture is as follows:

[0058] i. Weigh the dried (lyophilized) biopolymers (HA-MA and Gel SH) and mix them in the desired weight ratio in a vial.

[0059] ii. The lyophilized biopolymer was dissolved in saline, spun (2000 g, 10 s) within 5 min of adding saline, and incubated at 37°C in the dark until the biopolymer was completely dissolved to form a clear solution (approximately 10-15 min).

[0060] iii. Add photoinitiator solution to the biopolymer solution.

[0061] The corresponding liquid biopolymer mixture was converted into a cross-linked hydrogel by exposure to white light. Formulation 1 was exposed to an intensity of about 100 mW / cm 2 Formulation 2 was exposed to light with an intensity of about 10 mW / cm 2 light for about 10 minutes.

[0062] For hydrogels used as HRC, the ideal Gel-SH hydrogel has physical properties similar to those of natural corneal tissue. As shown in the following examples, the above formulations are shown to have physical properties similar to and compatible with natural human cornea.

[0063] Example 2 - Hydrogel Physical Property Testing

[0064] Next, various physical properties of the hydrogel prepared according to Example 1 were tested, including the following properties:

[0065] Transparency - Hydrogels were prepared in triplicate in 96-well plates and the transmittance to visible light was assessed by recording the spectra in a plate reader (Enspire, Perkin-Elmer). The absorbance values ​​obtained were converted to transmittance by Beer Lambert's law and plotted using saline as reference. The average transmittance was obtained by averaging the values ​​obtained over the entire spectrum (400-700 nm).

[0066] Compression modulus - Cylindrical hydrogels with a diameter of 5 mm and a height of 1 mm were prepared and tested in a UTS instrument (BiSS mechanical tester) with a parallel plate fixture to evaluate the compression modulus. The hydrogels were compressed at a rate of 1 mm / min using a 44N load cell with a maximum compression of 50%. The values ​​of strain and load were recorded, and the compression modulus was calculated from the slope of the stress-strain curve using the linear region between 0.1 and 0.2 mm / mm strain.

[0067] Adhesion Strength - The adhesion strength of the hydrogel to biological tissue was evaluated according to the ASTM F2458-05 standard. Porcine skin tissue purchased from a local butcher shop was thoroughly cleaned to remove grease and then cut into 2.5 cm × 1.5 cm blocks. The skin tissue blocks were glued to a glass slide. An incision was made between two adjacent glass slides, the skin tissue was kept at a distance of 1 mm, and the gap was filled with 75 μl of pre-gel solution and then photo-cross-linked. The assembly was incubated in physiological saline for hydrogel equilibrium and then adhesion tested in a BiSS UTS instrument. The glass slide was fixed in a wedge clamp (without disturbing alignment). The assembly was stretched at a speed of 1 mm / min until adhesive or cohesive failure was observed. The adhesion strength was calculated according to the following relationship: (maximum load / cross-sectional area) × 1000.

[0068] Weight and volume swelling-Hydrogel discs were prepared in molds of specified geometry (5 mm diameter, 1 mm height) and incubated in saline, and swelling was evaluated by changes in weight and volume over time. Weight measurements were performed by soaking the hydrogel with excess saline and recording the weight at different time points. The swelling weight percentage % was measured using the following relationship: [(Wi-Wt) / Wt]×100. Where Wt is the weight recorded at different time points and Wi is the initial weight. When the dimensions are measured using a vernier caliper, the volume swelling is calculated by measuring the percentage increase in volume. The swelling volume percentage % is measured using the relationship [(Vt-Vi) / Vi]×100 where Vt is the volume recorded at different time points and Vi is the initial volume.

[0069] Degradation - The degradation rate of the hydrogel was determined by incubating the hydrogel at ambient temperature in 1X phosphate buffered saline (PBS) under constant shaking (350 rpm) and measuring the change in weight over time. The degradation medium was replenished every other day to avoid saturation, and the hydrogel samples were retrieved at predetermined time points and their weights were recorded after lyophilization at -110°C for 24 hours. The percentage of degradation was calculated using the relationship [(Wi-Wt) / Wt]×100. Where Wt is the dry weight at different time points, and Wi is the initial dry weight recorded on the day of sample preparation.

[0070] Rupture Pressure - The rupture pressure of a hydrogel, which is particularly indicative of its ability to withstand intraocular pressure, was measured using transplant-rejected cadaveric corneal tissue. The tissue was cleaned and a 2 mm full-thickness perforation was made in the center of the tissue. The perforation was filled with 8 μl of pregel solution and then photocrosslinked. The hydrogel-filled cornea was placed on the anterior chamber connected to a syringe pump. 1X PBS was flowed into the assembly at a constant rate of 0.5 ml / min until the hydrogel detached from the site or began to leak. The pressure was monitored using a wireless pressure sensor and the rupture pressure was determined by calculating the difference between the initial and final pressures (the maximum recorded value before detachment).

[0071] Refractive Index - The refractive index was measured using a digital refractometer (Hanna Instruments) where light passes through a prism in contact with the sample. An image sensor determines the critical angle at which light is refracted from the sample.

[0072] The obtained hydrogel has the following physical properties:

[0073] Table 1

[0074] natural cornea Recipe 1 Recipe 2 Gel-SH:HA-MA ratio (weight) n / a 100:60 120:50 transparency ~87% 86.06±1.3% 91.18±1.25% Compression modulus 100-300kPa 352.41±25.82kPa 346.49±18.76kPa Adhesion strength n / a 33.44±1.22kPa 35.18±14.71kPa Maximum swelling: weight n / a 9.38±3.11% (after 30min) 16.91±4.17% (after 30min) Maximum swelling: volume b / a 5.61±2.2% (after 30min) 9.15±2.70%(after 30min) degradation b / a 7.2±2.08% (within 4 weeks) 6.45±1.53% (within 6 weeks) Burst pressure 2.5kPa 27.57±8.2kPa Not measured Refractive Index 1.37 1.34±0.0001 1.34±0.001

[0075] The above physical properties show that the hydrogels produced according to the above formulations are comparable or better than conventional biopolymers in simulating human corneal properties. In particular, both Gel-SH hydrogel formulations 1 and 2 showed lower swelling (measured by weight and volume), had a compression modulus more similar to that of the natural cornea, and showed less degradation than conventional formulations. In addition, unexpectedly, the refractive index of Gel-SH hydrogel formulations 1 and 2 was essentially the same as that of the natural cornea (1.37 for the natural cornea and 1.34 for both formulations).

[0076] In an aqueous solution containing Gel-SH, HA-MA, and a photoinitiator, some spontaneous crosslinking is expected to occur, even under low light conditions. However, a slow rate of spontaneous crosslinking may be advantageous, allowing the mixture to remain in an uncrosslinked form until the mixture is applied to a desired location, such as a corneal injury. It was surprisingly found that Formulation 2 advantageously had a slower rate of spontaneous crosslinking, allowing the mixture to be sufficiently unstable to be easily applied to a corneal injury up to about 15 minutes after the mixture was prepared. In contrast, Formulation 1 was found to spontaneously crosslink at a faster rate, allowing the mixture to be sufficiently unstable to be easily applied to a corneal injury up to about 5 minutes after the mixture was prepared.

[0077] Example 3 - Biocompatibility of hCSSCs and hydrogels

[0078] For the Gel SH hydrogel to be used as HRC and produce scar-free tissue regeneration at the corneal wound site, it is important that the hydrogel keeps corneal stromal stem cells alive, as well as maintains their phenotype and helps the wound heal without scars, while gradually reaching a differentiated state. Therefore, the biocompatibility of the hydrogel was tested by encapsulating human corneal stromal stem cells (hCSSCs) with hydrogel and culturing the cells therein for four weeks. After three passages, hCSSCs were cultured on the surface of coverslips or within the hydrogel matrix. For coverslip culture, hCSSCs were cultured at 5000 cells / cm 2 For hydrogel culture, hCSSCs were seeded at a density of 3 × 10 6The inoculation density of 10 cells / ml was mixed into the liquid biopolymer preparation, and the mixture was then exposed to crosslinking to form a hydrogel. Thus, the crosslinked hydrogel became the culture medium for the hCSSCs encapsulated therein. The hydrogel was maintained at 37°C, 5% CO2 sterile conditions and monitored for 4 weeks. The cells on the coverslips or the hydrogels injected with cells were incubated in the culture medium recommended for CSSCs, and the culture medium was changed every three days.

[0079] Over a 4-week period, cell viability was assessed using Calcein AM / ethidium homodimer / DAPI staining. Figures 1A-1C The results of culture for 1 day ( Figure 1A )、2 weeks( Figure 1B ) and 4 weeks ( Figure 1C ) and then grown in coverslip culture. Figures 1D-1F The results of culture for 1 day ( Figure 1D )、2 weeks( Figure 1E ) and 4 weeks ( Figure 1F ) and 3D images of cells grown in hydrogel culture based on formulation 2 of Example 1. Figures 1D-1F As shown, the cell distribution within the hydrogel was uniform, and after 4 weeks in culture, more than 80% of the cell population showed survival, indicating that the hydrogel was compatible with human corneal stromal cells. In addition, compared with hCSSCs grown on coverslips,

[0080] Cell phenotype was assessed using CD90 / αSMA / DAPI staining. CD90 is a stromal stem cell biomarker, while the expression of αSMA by the cells will reflect their differentiation status into keratocytes or myofibroblasts. Figures 2A-2C The results of culture for 1 day ( Figure 2A )、2 weeks( Figure 2B ) and 4 weeks ( Figure 2C ) and top view of cells grown in coverslip culture. Figure 2D-2F Shown are top views and 3D images of cells cultured in hydrogel culture based on Formulation 2 of Example 1 after 1 day (FIG. 2D), 2 weeks (FIG. 2E), and 4 weeks (FIG. 2F) of culture. Staining showed that the stromal stem cells initially maintained a stromal stem cell phenotype, as shown by CD90 staining, and gradually transitioned to a differentiated state within 4 weeks, as shown by increased αSMA staining.

[0081] Example 4 - Biocompatibility of hCECs and hydrogels

[0082] For Gel-SH hydrogels to function as HRCs and produce scar-free tissue regeneration at corneal wound sites, it is also important that the hydrogels allow the growth of human corneal epithelial cells (hCECs). Gel-SH hydrogels (Formulation 2) were evaluated for providing a supportive surface for epithelial cell growth by seeding primary hCECs on the hydrogels and allowing a monolayer to form. 5 cells / cm 2 hCECs suspensions were seeded directly onto the hydrogel surface or coverslip control surface at a seeding density of 1.5 ng / ml. The cultures were maintained at 37°C, 5% CO2 under sterile conditions and monitored daily for one week. Cell confluence was assessed over a one-week period using phase contrast imaging and staining for tight junction markers (Zona occlusions-ZO1) and DAPI and rhodamine-conjugated phalloidin.

[0083] Figure 3A-3B Phase contrast images of hCEC cells grown on coverslip culture after 4 days are shown, comparing the Figure 3A ) and hydrogel surface ( Figure 3B This comparison shows that hCECs proliferate more robustly on the hydrogel surface, such that full confluence is achieved on the hydrogel surface but not on the coverslip surface by day 4.

[0084] Figures 4A-4C Shown are the cells grown on the coverslip surface and stained with DAPI ( Figure 4A )、ZO1( Figure 4B ) and rhodamine phalloidin ( Figure 4C ) stained hCEC cells. Figures 4D-4F The cells grown on the surface of the hydrogel based on Formulation 2 of Example 1 and stained with DAPI ( Figure 4D )、ZO1( Figure 4E ) and rhodamine phalloidin ( Figure 4F Comparison of ZO1 staining showed that growth on hydrogel surfaces promoted the formation of tight junctions in hCECs at day 4 of culture, whereas growth on coverslips did not.

Claims

1. A biopolymer formulation comprising: Thiolated gelatin having an average molecular weight of 50-200 kDa and an average degree of substitution of about 0.2 mmol / g to about 1.2 mmol / g; and Methacrylated hyaluronic acid has an average molecular weight of 20-80 kDa and an average degree of substitution of about 0.5 mmol / g to about 1 mmol / g.

2. The biopolymer formulation of claim 1, wherein the average degree of substitution of the thiolated gelatin is from about 0.3 mmol / g to about 0.8 mmol / g.

3. The biopolymer formulation of claim 1 or claim 2, wherein the average degree of substitution of the thiolated gelatin is from about 0.6 mmol / g to about 0.8 mmol / g.

4. The biopolymer formulation of any one of claims 1-3, wherein the thiolated gelatin is from about 100 bloom to about 300 bloom.

5. The ophthalmic preparation of claim 4, wherein the thiolated gelatin is from about 200 bloom to about 250 bloom.

6. The biopolymer formulation of any one of claims 1-5, wherein the methacrylated hyaluronic acid has an average molecular weight of about 30 kDa to about 45 kDa.

7. The biopolymer formulation of claim 6, wherein the methacrylated hyaluronic acid has an average molecular weight of about 33 kDa.

8. The biopolymer formulation of any one of claims 1-7, wherein the average degree of substitution of the methacrylated hyaluronic acid is from about 0.7 mmol / g to about 0.9 mmol / g.

9. The biopolymer formulation of any one of claims 1 to 8, wherein the methacrylated hyaluronic acid and the thiolated gelatin are in the form of dry powders.

10. The biopolymer formulation of any one of claims 1-8, wherein the biopolymer formulation comprises a saline solution and at least one photoinitiator compound, and wherein the thiolated gelatin, the methacrylated hyaluronic acid, and the at least one photoinitiator compound are dissolved in the saline solution.

11. The biopolymer formulation of claim 10, wherein the biopolymer formulation is in the form of a liquid or a hydrogel.

12. The biopolymer formulation of claim 10 or claim 11, wherein the at least one photoinitiator compound comprises Eosin Y and triethanolamine.

13. The biopolymer formulation of any one of claims 10-12, wherein the biopolymer formulation comprises the thiolated gelatin at a concentration of about 50 mg / ml to about 140 mg / ml.

14. The biopolymer formulation of claim 13, wherein the biopolymer formulation comprises the thiolated gelatin at a concentration of about 90 mg / ml to about 130 mg / ml.

15. The biopolymer formulation of any one of claims 10-14, wherein the biopolymer formulation comprises the methacrylated hyaluronic acid at a concentration of about 40 mg / ml to about 90 mg / ml.

16. The biopolymer formulation of claim 15, wherein the biopolymer formulation comprises the methacrylated hyaluronic acid at a concentration of about 45 mg / ml to about 65 mg / ml.

17. The biopolymer formulation of any one of claims 1-15, wherein the weight ratio of the thiolated gelatin to the methacrylated hyaluronic acid is from about 100:30 to about 100:

70.

18. The biopolymer formulation of any one of claims 1-17, wherein the biopolymer formulation comprises a therapeutic agent.

19. The method of claim 18, wherein the therapeutic agent is a therapeutic exosome.

20. A method of treating a corneal disease or injury in a subject, the method comprising: providing a liquid biopolymer mixture comprising at least one photoinitiator compound; applying the liquid biopolymer mixture to a cornea of ​​a subject; as well as exposing the liquid biopolymer mixture applied to the cornea to light with a wavelength within the excitation range of at least one photoinitiator compound, wherein the liquid biopolymer mixture comprises: Thiolated gelatin having an average molecular weight of 50-200 kDa and an average degree of substitution of 0.2-1.2 mmol / g; and Methacrylated hyaluronic acid has an average molecular weight of 20-80 kDa and an average degree of substitution of 0.5-1 mmol / g.

21. The method of claim 20, wherein the at least one photoinitiator compound comprises Eosin Y and triethanolamine, and the light is white light.

22. The method of claim 20 or 21, wherein the liquid biopolymer mixture is prepared by mixing a dry biopolymer premix comprising the thiolated gelatin and the methacrylated hyaluronic acid with a photoinitiator solution comprising at least one photoinitiator compound dissolved in a saline solution.

23. The method of any one of claims 20-22, wherein the liquid biopolymer mixture comprises a therapeutic agent.

24. The method of claim 23, wherein the therapeutic agent is a therapeutic exosome.

25. A biopolymer formulation comprising: Thiolated gelatin having a bloom value of about 200 bloom to about 275 bloom and an average degree of substitution of about 0.5 mmol / g to about 0.9 mmol / g; and Methacrylated hyaluronic acid having an average molecular weight of 25-40 kDa and an average degree of substitution of about 0.7 mmol / g to about 0.9 mmol / g, The weight ratio of the thiolated gelatin to the methacrylated hyaluronic acid is about 100:30 to about 100:

70.

26. The biopolymer formulation of claim 25, wherein: The bloom value of the thiolated gelatin is about 220 bloom to about 230 bloom, and the average degree of substitution is about 0.5 mmol / g to about 0.7 mmol / g, and The weight ratio of the thiolated gelatin to the methacrylated hyaluronic acid is about 100:55 to about 100:

65.

27. The biopolymer formulation of claim 25, wherein: The bloom value of the thiolated gelatin is about 240 bloom to about 260 bloom, and the average degree of substitution is about 0.7 mmol / g to about 0.9 mmol / g, and The weight ratio of the thiolated gelatin to the methacrylated hyaluronic acid is about 100:35 to about 100:

45.

28. The biopolymer formulation of any one of claims 25-27, wherein the methacrylated hyaluronic acid and the thiolated gelatin are in the form of dry powders.

29. The biopolymer formulation of any one of claims 25-27, wherein the biopolymer formulation comprises a saline solution and at least one photoinitiator compound, and wherein the thiolated gelatin, the methacrylated hyaluronic acid, and the at least one photoinitiator compound are dissolved in the saline solution.

30. The biopolymer formulation of claim 29, wherein the biopolymer formulation is in the form of a liquid or a hydrogel.

31. The biopolymer formulation of claim 29, wherein the at least one photoinitiator compound comprises Eosin Y and triethanolamine.

32. The biopolymer formulation of any one of claims 29-31, wherein the biopolymer formulation comprises the thiolated gelatin at a concentration of about 90 mg / ml to about 130 mg / ml.

33. The biopolymer formulation of any one of claims 29-32, wherein the biopolymer formulation comprises the methacrylated hyaluronic acid at a concentration of about 40 mg / ml to about 70 mg / ml.